2012
DOI: 10.5539/ies.v5n6p65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Pattern and Body Mass index on the Academic Performance of In-school Adolescents

Abstract: The main objective of this study was to determine the effects of dietary pattern and body mass index on the academic performance of in-school adolescents in Ekiti State. One hundred and twenty eight students (10-19 years) selected from three senior secondary schools in Ekiti State Nigeria, formed the participants for this study. Questionnaire was the instrument for data collection and the data were subjected to descriptive and inferential statistics (bivariate Pearson correlation analysis and linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…A total of six studies reported significant associations for fruit and vegetables with academic achievement. For those studies that reported a correlation, a consistent positive relationship was demonstrated between fruit and vegetable consumption and academic achievement, with values ranging from r = 0.195 to 0.23 (53) [odds ratio = 1.61 (1.11-2.32)] (34) (r = 0.23) (25,32,33,40,47) for adequate amounts of fruit and vegetables (40,53) . Two studies reported on fruit only with increases in academic achievement (32,47) .…”
Section: Fruit and Vegetablesmentioning
confidence: 88%
See 2 more Smart Citations
“…A total of six studies reported significant associations for fruit and vegetables with academic achievement. For those studies that reported a correlation, a consistent positive relationship was demonstrated between fruit and vegetable consumption and academic achievement, with values ranging from r = 0.195 to 0.23 (53) [odds ratio = 1.61 (1.11-2.32)] (34) (r = 0.23) (25,32,33,40,47) for adequate amounts of fruit and vegetables (40,53) . Two studies reported on fruit only with increases in academic achievement (32,47) .…”
Section: Fruit and Vegetablesmentioning
confidence: 88%
“…For those studies that reported a correlation, a consistent positive relationship was demonstrated between fruit and vegetable consumption and academic achievement, with values ranging from r = 0.195 to 0.23 (53) [odds ratio = 1.61 (1.11-2.32)] (34) (r = 0.23) (25,32,33,40,47) for adequate amounts of fruit and vegetables (40,53) . For those studies that reported a correlation, a consistent positive relationship was demonstrated between fruit and vegetable consumption and academic achievement, with values ranging from r = 0.195 to 0.23 (53) [odds ratio = 1.61 (1.11-2.32)] (34) (r = 0.23) (25,32,33,40,47) for adequate amounts of fruit and vegetables (40,53) .…”
Section: Fruit and Vegetablesmentioning
confidence: 91%
See 1 more Smart Citation
“…Adolescence is a period of rapid development that requires the ingestion of essential nutrients from foods to cover the harmonious developmental needs of the body. Failure to achieve this demand often results in varying degrees of malnutrition that has an impact on the health and academic performance of adolescents [1]. The association between nutritional status and knowledge of certain sociodemographic and economic characteristics has been the focus of several relevant studies [4].…”
Section: Introductionmentioning
confidence: 99%
“…For these teenagers, their intellectual capacity needs to be enhanced to better respond and perform well [1]. Indeed, school performance expressed by school performance is a multifactorial process conditioned by multiple factors that depend on the child, such as his / her state of health, nutritional and neurocognitive development, and sociodemographic and socio-economic characteristics of the household, the quality and experience of the school [2,3].…”
Section: Introductionmentioning
confidence: 99%